The changing landscape of regional trade agreements: 2006 Update - Roberto V. Fiorentino; Luis Verdeja; Christelle Toqueboeuf (World Trade Organization (WTO), 2007)
Regional Trade Agreements (RTAs) are a prominent feature of the multilateral trading system (MTS) and have become an important trade policy tool for virtually all WTO Members. The number of RTAs as well as the world share of trade covered under them has been steadily increasing over the last ten years and this trend will be further strengthened by the many RTAs being proposed and those currently under negotiation; the impasse in the Doha Round exacerbates the gap between the preferential and the MFN paths to trade liberalization. The proliferation of RTAs presents WTO Members with challenges and opportunities; the promotion of free trade through preferential agreements can foster trade liberalization and benefit economic development by integrating developing countries into the world economy; yet the development of complex networks of non-MFN trade relations will increase discrimination and may well undermine transparency and predictability in international trade relations; it is therefore of systemic importance for the MTS that the WTO addresses this dichotomy and ensures that RTAs are designed and implemented so to complement and not undermine the multilateral process. This paper sets out the scene for such discussion by providing an update of recent developments, trends and future directions of the so called "Changing Landscape of RTAs". Two broad themes are explored: "RTAs' kaleidoscope" maps the global landscape of RTAs and looks at main trends and characteristics of "RTA proliferation" through quantitative and qualitative categorizations of RTAs. The second section of this paper focuses on the WTO-RTA relationship and its systemic implications for the MTS; it identifies some of the current and potential tensions arising from the coexistence of the two systems and it provides an insight into multilateral efforts being pursued to address the existing unbalances.
Keywords: 330; custom union (CU); economic integration agreement (EIA); free trade agreement (FTA); regional trade agreements (RTAs)